Pengaruh Penggunaan Literasi Digital terhadap Kreativitas Belajar PAK Siswa Kelas XII SMA Negeri 1 Balige Kabupaten Toba Tahun Pembelajaran 2023/2024 - Nopitasari Simamora; Rida Gultom; Maria Widiastuti; Frainskoy Rio Noibaho (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study was to determine whether there is a positive and significant influence between the Use of Digital Literacy on PAK Learning Creativity of Class XII SMA Negeri 1 Balige Toba Regency Learning Year 2023/2024. The research method used is quantitative inferential statistical method. The population is class XII students of SMA Negeri 1 Balige Toba Regency who are Protestant Christians totaling 286 people and a sample of 43 people was determined using the Random Sample technique. Data were collected using a positive closed questionnaire of 40 items, namely 20 items for variable X and 20 items for variable Y. The results of data analysis show that there is a positive and significant influence between the Use of Digital Literacy on PAK Learning Creativity of Class XII Students of SMA Negeri 1 Balige Toba Regency Learning Year 2023/2024: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.559> rtable (a=0.05, n=43) = 0.301. b) Significant relationship test obtained tcount = 4.322> ttable (a=0.05, dk=n-2=41) = 2.021. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = “7.00”+0.60X. b) Regression determination coefficient test (r2) = 31.3%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 12, dk denominator = n-2 = 43-2 = 41), namely 18.68> 2.00. Thus Ha, namely there is a positive and significant influence on the use of literacy d. b) Test the regression determination coefficient (r2) = 31.3%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 12, dk denominator = n-2 = 43-2 = 41), namely 18.68> 2.00. Thus Ha, namely that there is a positive and significant effect of the use of digital literacy on the learning creativity of XII grade students of SMA Negeri 1 Balige, Toba Regency for the 2023/2024 Learning Year, is accepted and H0 is rejected.